Modelagem de processos e a metodologia IDEF: proposta de um ambiente colaborativo na produção de biodiesel - Oliveira, Josele Nara Delazeri de (2010)
Economic development is of utmost importance for any nation or locality, however, recognizing that natural resources are finite, such development must be associated to environment preservation. Most of the energy consumed in the world comes from the oil, coal and natural gas. These sources are limited and with forecast of exhaustion in the future, therefore, the search for alternative energy sources is of utmost importance. With this in mind, energy matrix that are able to substitute fossil fuels become a relevant world-wide issue. Brazil is the country with the largest biodiversity, which explains its wealth in oleaginous. However, it´s production is restricted to nutritional means, disregarding some species with high lipidic content. Biodiesel is a worthy alternative, being a renewable and biodegradable fuel. This research had the objective of developing a general descriptive model, having as base the IDEF0 methodology (Integration Definition Language for Function Modeling) and to propose a cooperative environment among the different actors of the biodiesel productive chain. The study had as base an IDEF0 modeling technique, with the purpose of understanding and describing the main processes involved in the biodiesel productive chain, aiming at suggestions of improvement in the relationship among the different actors of this chain, in order to optimize the management process. The results showed that the viability of long term biodiesel production depends on infrastructure, qualified man power, governmental rendering of services associated with production and governmental incentives. Faced with the reality presented in the research, a transition to free market was identified as a form of reducing costs of production and transportation for the producing companies. As well as the incentive to export, in order to lessen the excess of productive capacity not adequate to the demand. The auctions were created as a form of guaranteeing the commercialization of the biodiesel produced, however, with market more mature there´s a need to rethink these auctions. The IDEF0 Diagram for its simple and visual characteristic enabled the understanding of the function of each actor in the biodiesel productive chain and the identification of important elements, allowing suggestions of improvement in communication between the involved parts. For the agility and precision demanded nowadays, a computer system can be implanted, integrating the entire productive chain. For this, it is suggested in addition to IDEF0, the use of IDEF3, that describes the processes and its Inter-relations in a much more detailed form.